Research Progress of Flexible Wearable Devices in Rehabilitation Medicine - Zijun HE; Qing ZENG; Ze GONG; Rong CHEN; Hang QU; Shilin LI; Pengcheng LU; Jihua ZOU; Guozhi HUANG (康复学报)
With the development of Internet of things, the healthcare service is getting intelligent and wearable devices have become the focus of healthcare. In the field of healthcare, wearable devices are mainly applied in health monitoring, motion sensing, big health analysis, and so on. All these applications make wearable devices a good tool to achieve the ultimate goal of rehabilitation medicine, which is function recovery and health promotion, thus wearable devices are meant to play an important role in rehabilitation medicine. The users will have a high demand for the comforts and designs of the wearable devices because the wearable devices need to be worn for a long period in the skin; however, traditional devices are unable to satisfy the demand so that novel materials are needed. Nowadays, the wearable devices sold in the market such as smart watches and smart glasses are made of rigid materials, which have poor ductility and high density, thus they are difficult to satisfy the demand of users for comforts and convenience. Flexible materials are novel materials with good portability, high ductility, and could keep stable physicochemical properties even if in the process of extension. The wearable devices made of flexible materials inherit the advantages of flexible materials so that they might make up for the shortcomings of traditional wearable devices and then be widely applied in the field of rehabilitation medicine. As is shown in the domestic and foreign literature, flexible wearable devices have the potential for clinical application. Compared with traditional devices, flexible wearable devices not only improve user experience but also offer more powerful functions to meet a variety of clinical demands. In this review, we briefly introduce the principle and classification of flexible wearable devices and review the research progress of the application of flexible wearable devices in the field of rehabilitation medicine from six aspects: health monitoring, motion monitoring, swallow-speech monitoring, home rehabilitation, fall warning, and intelligent rehabilitation. Finally, we summarize current challenges and recent development trends of flexible wearable devices to provide a theoretical basis for future clinical applications